Research trends on Smart Transportation policy in Asia and Europe: A Biblioetric Analysis - Fitriani (Jurnal Studi Pemerintahan, 2023)
Smart transportation policy research has evolved over the last decade following increasingly complex changes and challenges. Therefore, the purpose of this paper is to use a scoping review and bibliometric analysis to examine all publications on smart transportation policy, particularly on the Asian Continent and the European Continent. A total of 823 smart transporta- tion policy articles indexed in the Scopus database were analyzed through scoping reviews and bibliometric analysis. Articles are analyzed based on the number of publications per year, contributing countries, field of study, authors, documents cited, related issues, and papers cited. Next, Citespace is used to provide a visual analysis of keyword co-occurrence. The results of this study indicate that publications related to the Smart Transportation Policy continue to increase every year. The continent that has the highest number of publications is dominated by the Asian continent, namely China with a total of 201, followed by the European continent, namely Italy with a total of 81. Although the area of analysis is only on the Asian continent and the European continent, the United States and several countries in the Americas have seriously contributed to the topic.